Analisis Strategi Pemasaran dalam Upaya Meningkatkan Penjualan Poklahsar Kinar Djaya - Nurhaliza, Rida; Suryana, Agus Asep Handaka; Mahdiana, Izza (Universitas Galuh, 2025)
The Fish Consumption Rate (AKI) in Bandung City from 2019 to 2023 only reached 48.32 kg/capita/year, which is relatively lower compared to other regions, such as Bekasi City and Depok City. The low Fish Consumption Rate (AKI) poses a challenge for Poklahsar Kinar Djaya, as fresh fish marketing groups in Bandung City, which have also experienced a decline in revenue since the Covid-19 pandemic. The objective of this research is to identify and analyze the market environment and formulate marketing strategies that can be applied by Poklahsar Kinar Djaya. The research was conducted from February to August 2024. The research method used is a case study method with data collection through questionnaires, interviews, observations, and literature studies. Data analysis was performed using the Business Model Canvas, IFAS and EFAS Matrix Analysis, IFE and EFE Matrices, and SWOT Matrix. Based on the research conducted, the position of Poklahsar Kinar Djaya is in the Hold and Maintain strategy, which indicates that business growth and development are facing significant threats and require diversification strategies. This situation suggests that fish sales have strong potential but need to be further enhanced to mitigate the threats. Strategies that can be implemented include optimizing digital marketing strategies, enhancing branding and personal selling, and diversifying suppliers.